Stem cell‐derived extracellular vesicles reduce the expression of molecules involved in cardiac hypertrophy—In a model of human-induced pluripotent stem cell-derived cardiomyocytes - Constantin, Alina; Comarița, Ioana Karla; Alexandru, Nicoleta; Filippi, Alexandru; Bojin, Florina; Gherghiceanu, Mihaela; Vîlcu, Alexandra; Nemecz, Miruna; Niculescu, Loredan Stefan; Păunescu, Virgil; Georgescu, Adriana (Frontiers in Pharmacology, 2022)
Cardiac pathological hypertrophy is the major risk factor that usually progresses to heart failure. We hypothesized that extracellular vesicles (EVs), known to act as important mediators in regulating physiological and pathological functions, could have the potential to reduce the cardiac hypertrophy and the ensuing cardiovascular diseases. Herein, the effects of mesenchymal stem cell-derived extracellular vesicles (EVs-MSCs) on cardiac hypertrophy were investigated. EVs were isolated from the secretome of human adipose tissue-derived stem cells (EV-ADSCs) or bone marrow-derived stem cells (EV-BMMSCs). Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were stimulated with AngII and TGF-β1, in absence or presence of EVs. The results showed that exposure of hiPSC-CMs to AngII and TGF-β1 generated in vitro model of hypertrophic cardiomyocytes characterized by increases in surface area, ROS production, protein expression of cardiac-specific biomarkers ANF, MIF, cTnI, COL1A1, Cx43, α-SMA and signalling molecules SMAD2 and NF-kBp50. The presence of EV-ADSCs or EV-BMMSCs in the hiPSC-CM culture along with hypertrophic stimuli reduced the protein expressions of hypertrophic specific markers (ANF, MIF, cTnI, COL1A1) and the gene expressions of IL-6 molecule involved in inflammatory process associated with cardiac hypertrophy and transcription factors SMAD2, SMAD3, cJUN, cFOS with role in cardiomyocyte hypertrophic response induced by AngII and TGF-β1. The EV-ADSCs were more effective in reducing the protein expressions of hypertrophic and inflammatory markers, while EV-BMMSCs in reducing the gene expressions of transcription factors. Notably, neither EV-ADSCs nor EV-BMMSCs induced significant changes in cardiac biomarkers Cx43, α-SMA and fibronectin. These different effects of stem cell-derived EVs could be attributed to their miRNA content: some miRNAs (miR-126-3p, miR-222-3p, miR-30e-5p, miR-181b-5p, miR-124-3p, miR-155-5p, miR-210-3p hsa-miR-221-3p) were expressed in both types of EVs and others only in EV-ADSCs (miR-181a-5p, miR-185-5p, miR-21-5p) or in EV-BMMSCs (miR-143-3p, miR-146a-5p, miR-93-5p), some of these attenuating the cardiac hypertrophy while others enhance it. In conclusion, in hiPSC-CMs the stem cell-derived EVs through their cargo reduced the expression of hypertrophic specific markers and molecules involved in inflammatory process associated with cardiac hypertrophy. The data suggest the EV potential to act as therapeutic mediators to reduce cardiac hypertrophy and possibly the subsequent cardiovascular events.